Evaluation of the Factors Affecting the Mortality Rate in Poultry Transport via Panel Data Analysis - Tekindal, M. A.; Mat, B.; Cevrimli, M. B.; Akin, A. C.; Ozel, Z.; Arikan, M. S. (Facta-Fundacio Arnco Ciencia Tecnologia Avicolas, 2023)
In this study, we evaluated some of the factors that affect mortality rate during transport from broiler poultry houses to slaughterhouses by conducting panel data analysis. We analyzed the data obtained from 26,599 broiler farms transported to the slaughterhouse from contracted broiler farms in 11 provinces in Turkey. Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) tests were performed to evaluate whether the series forming the dataset were stationary. To analyze individual effects, parameters were estimated using fixed and random effects models. To decide which of the two models was valid, the Hausman test and fixed effects panel data analysis were performed. The fixed effects model explained 90.93% of the changes in the mortality rate through the independent variables. In the non-periodical fixed-effect panel data analysis, the mortality rate shows a significant (p<0.01) effect between the number of animals alive, number of animals dead, mean and total live weight at poultry farm exit, mean live weight at slaughterhouse arrival, and different variables. Our results showed that the estimation equations developed using model parameters to determine the mortality rate during transportation from different provinces could contribute to effective production planning.
Keywords: Poultry; transportation; panel data; Turkey; mortality rate